Několik poznámek k problému humanizace technického vzdělávání - Tulka, Jiří (Univerzita Pardubice, 1998)
The process of humanization of the education process has its objective causes. It is necassary to search for its motivation impulses in the field of the progressively developing material technology and its impact on the life of the society. Under the influence of the technical development the biosphere gradually transforms into noosphere (Vernadskij) and the fact that most of the human population lives in the noosphere, sets till new and new tasks for the technical and social science. Thus, in the broader sense, it is necessary to understand the conception of the technical science as the one of social science.
Keywords: humanizace; noosféra; společenské vědy; technické vědy; technosféra; Vzdělávání